Effective recruitment strategies in primary care research: A systematic review - Ngune, Irene; Jiwa, Moyez; Dadich, A.; Lotriet, J.; Sririam, Deepa (Radcliffe Medical Press Ltd., 2012)
Background: Patient recruitment in primary care research is often a protracted and frustrating process, affecting project timeframes, budget and the dissemination of research findings. Yet, clear guidance on patient recruitment strategies in primary care research is limited. This paper addresses this issue through a systematic review. Method: Articles were sourced from five academic databases – AustHealth, CINAHL, the Cochrane Methodology Group, EMBASE and PubMed/Medline; grey literature was also sourced from an academic library and the Primary Healthcare Research & Information Service (PHCRIS) website. Two reviewers independently screened the articles using the following criteria: (1) published in English, (2) reported empirical research, (3) focused on interventions designed to increase patient recruitment in primary care settings, and (4) reported patient recruitment in primary care settings.Results: Sixty-six articles met the inclusion criteria. Of these, 23 specifically focused on recruitment strategies and included randomised trials (n = 7), systematic reviews (n = 8) and qualitative studies (n = 8). Of the remaining articles, 30 evaluated recruitment strategies, while 13 addressed the value of recruitment strategies using descriptive statistics and/or qualitative data. Among the 66 articles, primary care chiefly included general practice (n = 30); nursing and allied health services, multiple settings, as well as other community settings (n = 30); and pharmacy (n = 6). Effective recruitment strategies included the involvement of a discipline champion, simple patient eligibility criteria, patient incentives and organisational strategies that reduce practitioner workload. Conclusion: The most effective recruitment in primary care research requires practitioner involvement. The active participation of primary care practitioners in both the design and conduct of research helps to identify strategies that are congruent with the context in which patient care is delivered. This is reported to be the optimal recruitment strategy.